Hydrometeorological Drought Hazard and Vulnerability Assessment for Northern Bulgaria - Radeva, Kalina; Nikolova, Nina (Geographica Pannonica, 2020)
In recent years, threats of natural origin, including those associated with the occurrence of drought is a topic that arouses interest in representatives of local government agencies, federal governmental authorities, scientific communities and residents of cities and villages. A significant part of the economy of Northern Bulgaria is agricultural, which increases the need for careful water management and planning. The aim of this study is to identify the drought hazard with regard to its spatial extends, frequency and severity and to assess the vulnerability to drought in Northern Bulgaria at the regional scale (NUTS-2). The standardized precipitation index (SPI), Standardised Precipitation-Evapotranspiration Index (SPEI) and Streamflow Drought Index (SDI) at 12-month time step for the period 1961–2012 were used to obtain drought hazard index (DHI). In order to assess drought vulnerability, Drought Vulnerability Index (DVI) was calculated based on the following parameters: population density, municipal water use, industrial water use, agricultural water use, and public water services. The results of the study show low DHI values and homogeneous distribution of drought hazard in the north part of Bulgaria. However, the drought vulnerability in the investigated area is very high due to the higher consumption of water by industry, municipal water supply, and extensive agricultural lands. Our results provide an elaborated understanding of the drought hazard and drought vulnerability and will be helpful as an early step in the development of risk-based drought management plans.